2019
DOI: 10.1021/acsenergylett.9b00251
|View full text |Cite
|
Sign up to set email alerts
|

Slow Carrier Cooling in Hybrid Pb–Sn Halide Perovskites

Abstract: Experimental methods, fluence dependent pump-probe signal, fluence dependence kinetics, fitting of high energy tail of pump-probe spectra (link).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 35 publications
(98 reference statements)
3
60
3
Order By: Relevance
“…The carrier temperatures determined in this way are plotted in dark blue as cooling curves in Figure 2B,C, for two different excitation fluences. The initial temperatures from our measurements are around 450 K, which is somewhat colder than in several previous reports for similar initial carrier densities across a range of metal halide compositions, but on the same order of magnitude in many cases, 22,24,26,34,62 with only a few reports of temperatures exceeding 1000 K. 28, 30,35 Lower…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 46%
“…The carrier temperatures determined in this way are plotted in dark blue as cooling curves in Figure 2B,C, for two different excitation fluences. The initial temperatures from our measurements are around 450 K, which is somewhat colder than in several previous reports for similar initial carrier densities across a range of metal halide compositions, but on the same order of magnitude in many cases, 22,24,26,34,62 with only a few reports of temperatures exceeding 1000 K. 28, 30,35 Lower…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 46%
“…Verma et al showed a two-stage carrier cooling dynamics in a series of MAPb 1−x Sn x I 3 perovskites. [150] The cooling rate can be found to be slower than that of pure Pb systems. The first stage involves a monotonic slowdown of Fröhlich interactions between carriers and metal-iodide bonds as the Sn content increases while the second stage deals with the decay of optical phonon into acoustic phonons which is slowest at 60% Sn content.…”
Section: Mixed Tin Halide Perovskitesmentioning
confidence: 95%
“…Therefore, to improve their suitability, the fundamental dynamics of carriers in the materials must be understood. Verma et al showed a two‐stage carrier cooling dynamics in a series of MAPb 1− x Sn x I 3 perovskites . The cooling rate can be found to be slower than that of pure Pb systems.…”
Section: Photophysical Properties Of Sn Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Pb-Sn alloyed PVSKs, a slower cooling process can be observed with the increasing of the Sn content revealed by Verma and coworkers. 123 The believed the Sn addition would influence all the three stages of the cooling process. First, increasing Sn content would increase carrier density along with stronger carrier-carrier scattering.…”
mentioning
confidence: 99%